Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Q. Prove

$$\frac{(5^{x-1}+5^{x+1})^2}{25^{x-1}+25^{x+1}}=\frac{338}{313}$$

My try: expand and got:

$$\frac{5^{2x-2}+2(5^{x^2-1})+5^{2x+2}}{5^{2x-2}+5^{2x+2}}$$

Now what? I find my pre-calculus skills esp with Indices, Logarithms & Trigo lacking ... need to know how to apply the formulas more

share|improve this question
4  
$5^{x^2-1}$ is not correct, you should have there $5^{(x+1)+(x-1)}=5^{2x}$. \\ Hint for the original problem: Try to factor out $5^{2x}$ or $5^{2x-2}$ or something similar in both numerator and denominator. –  Martin Sleziak Jan 25 '12 at 9:53
    
@MartinSleziak, ah I am always confused about the +-*/ stuff ... –  Jiew Meng Jan 25 '12 at 10:13

3 Answers 3

up vote 4 down vote accepted

Let $u=5^x$. Then $u^2=25^x$ and $$ \frac{(5^{x-1}+5^{x+1})^2}{25^{x-1}+25^{x+1}}=\frac{(u/5+5u)^2}{u^2/25+25u^2}=\frac{u^2(1/5+5)^2}{u^2(1/25+25)}=\frac{(1/5+5)^2}{(1/25+25)}=\frac{338}{313} $$

share|improve this answer
    
OH nice, but can you factorise $(u/5+5u)^2 = u^2(1/5+5)^2$? –  Jiew Meng Jan 25 '12 at 10:41
    
Oops, you were faster than me at writing your own idea! –  Gigili Jan 25 '12 at 10:42
1  
@jiewmeng, $(u/5+5u)^2 = (u(1/5+5))^2 = u^2(1/5+5)^2$. –  lhf Jan 25 '12 at 10:48
    
I also tried substituting $u = 5^={2x}$ just now but got a wrong answer, why is that? i.imgur.com/tpDJ3.png –  Jiew Meng Jan 25 '12 at 11:05
    
@jiewmeng, the denominator in the last line but one should be $u+5^4u$. –  lhf Jan 25 '12 at 11:11

Factor as: $$\frac{(5^{x-1}+5^{x+1})^2}{25^{x-1}+25^{x+1}}=\frac{(5^{x-1})^2(1+5^2)^2}{(5^{x-1})^2(1+25^2)}$$

Then simplify.

share|improve this answer
    
How did you the the "non-x" (right most, no x variables) part? –  Jiew Meng Jan 25 '12 at 10:08
    
I am not sure I understand what you mean. Do you mean why ${(5^{x-1}+5^{x+1})^2}={(5^{x-1})^2(1+5^2)^2}$? . This simply follows from $5^{x+1}=(5^2)5^{x-1}$. You can reason similarly for the denominator. –  user22705 Jan 25 '12 at 10:23
    
Then $(5^2)5x−1 = (1+5^2)^2$ how did you get this? Sorry, I am abit blur here –  Jiew Meng Jan 25 '12 at 10:31
2  
everything i squared in the numerator. remember that $(ab+ac)^2=a^2(b+c)^2$. –  user22705 Jan 25 '12 at 10:39

To find $x$ from

$\displaystyle\frac{5^{2x-2}+2(5^{2x})+5^{2x+2}}{5^{2x-2}+5^{2x+2}}=\frac{338}{313}$

i.e.

$\displaystyle 1+\frac{2\times 5^{2x}}{5^{2x-2}+5^{2x+2}}=1+\frac{25}{313}$

i.e.

$\displaystyle\frac{2\times 5^{2x}}{5^{2x-2}+5^{2x+2}}=\frac{25}{313}$

i.e. $\displaystyle\frac{2}{5^{-2}+5^2}=\frac{25}{313}$, an identity. So the above equation is valid for all $x\epsilon \mathbb{R}$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.